Variables associated with pulmonary hypertension screened by echocardiography in chronic myeloid leukemia patients on dasatinib therapy - Jin, Wenying; Yang, Sen; Yu, Chao; Zhu, Tiangang; Jiang, Qian (Frontiers in Cardiovascular Medicine, 2022)
Background Pulmonary hypertension (PH) is a rare but life-threatening adverse event (AE) of dasatinib, but the associated variables are not clear. This study aimed to explore the variables associated with PH by echocardiography in patients with chronic myeloid leukemia in the chronic phase (CML-CP) receiving dasatinib therapy. Methods Echocardiography was performed to estimate the probability of PH and pulmonary artery systolic pressure (PASP). Binary logistic analysis and Fine–Gray hazard model were used to identify the variables associated with PH by using cross-sectional and longitudinal data. Results Among the 243 patients in the cross-sectional dataset, with a median dasatinib therapy duration of 27 months, 30 (12.3%) were classified as having a high probability of PH. Increasing age (OR = 1.7, p = 0.002; OR = 1.5, p = 0.003) and pericardial effusion (OR = 4.3, p = 0.004; OR = 3.2, p = 0.014) were significantly associated with a high probability of PH and PASP ≥ 40 mmHg, respectively. Among the 161 patients in the longitudinal dataset, the 3-year cumulative incidences of a high probability of PH and PASP ≥ 40 mmHg were 9.3% and 22.1%, respectively. Pericardial effusion (HR = 3.8, p = 0.005) and cardiopulmonary comorbidities (HR = 3.2, p = 0.021) were significantly associated with a high probability of PH; increasing age (HR = 1.5, p < 0.001) and dasatinib as ≥ 3rd-line therapy (p = 0.032; 2nd-line vs. 1st-line, HR = 2.0, p = 0.200; ≥ 3rd-line vs. 1st-line, HR = 3.4, p = 0.047) were significantly associated with PASP ≥ 40 mmHg. Conclusion Increasing age, pericardial effusion, cardiopulmonary comorbidities, and dasatinib as ≥ 3rd-line TKI therapy were associated with PH in the patients with CML-CP on dasatinib therapy.